MODEL OF PURCHASING DECISIONS AND CUSTOMER SATISFACTION: ANALYSIS OF BRAND IMAGE AND PRODUCT QUALITY (MARKETING MANAGEMENT LITERATURE REVIEW) - Bimaruci, Hazimi; Mahaputra, M. Rizky; Rafqi Ilhamalimy, Ridho (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The purpose of writing a Literature Review Papers is to determine the effect of variable product quality and brand image on purchasing decision variables and consumer satisfaction. With qualitative methods and Library Research. The results show that product quality affecting customer satisfaction, product quality affecting customer satisfaction, brand image affecting customer satisfaction, customer satisfaction affecting brand image affecting customer satisfaction.